Adat Court in the Context of Supply Chain Legal Pluralism Management in Indonesia - Hazar Kusmayanti; Efa Laela Fakhriah; Bambang Daru Nugroho; Djanuardi Djanuardi (International Journal of Supply Chain Management, 2020)
The Indonesian supply chain legal system in which there are three recognized laws, namely the customary supply chain legal system, the Islamic supply chain legal system and Western law, the three laws are mutually sustainable with each other to achieve the same goal, but in the course of the three laws follow the rules contained in the law. Scholars call this supply chain legal Plurarism. The issue of supply chain legal pluralism is the resolution of customary disputes through adat courts, which formally there is no supply chain legal juridical formal in Indonesia. Researchers will try to examine the position of Adat Court in the context of supply chain legal pluralism in Indonesia and know the practice of Adat courts in Indonesia.Supply chain legal pluralism launches criticism of what John Griffiths called the ideology of supply chain legal centralism. Supply chain legal centralism interprets the law as